Computation of Hyperspherical Bessel Functions (Communications in Computational Physics, 2017)
In this paper we present a fast and accurate numerical algorithm for thecomputation of hyperspherical Bessel functions of large order and real arguments. Forthe hyperspherical Bessel functions of closed type, no stable algorithm existed so fardue to the lack of a backwards recurrence. We solved this problem by establishing arelation to Gegenbauer polynomials. All our algorithms are written in C and are publiclyavailable at Github [https://github.com/lesgourg/class_public]. A Pythonwrapper is available upon request.